2019
DOI: 10.1038/s41598-018-37688-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional annotation of putative QTL associated with black tea quality and drought tolerance traits

Abstract: The understanding of black tea quality and percent relative water content (%RWC) traits in tea (Camellia sinensis) by a quantitative trait loci (QTL) approach can be useful in elucidation and identification of candidate genes underlying the QTL which has remained to be difficult. The objective of the study was to identify putative QTL controlling black tea quality and percent relative water traits in two tea populations and their F1 progeny. A total of 1,421 DArTseq markers derived from the linkage map identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…One thousand four hundred and twenty-one DArTseq markers derived from C. sinensis genomic DNA of the two parents and 261 F 1 progeny were subjected to linkage mapping analyses using JoinMap 4.0 (Van Ooijen 2006) and QTL mapping analyses using MapQTL 6.0 software (Van Ooijen et al , 2000) as described previously (Koech et al 2018; Koech et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…One thousand four hundred and twenty-one DArTseq markers derived from C. sinensis genomic DNA of the two parents and 261 F 1 progeny were subjected to linkage mapping analyses using JoinMap 4.0 (Van Ooijen 2006) and QTL mapping analyses using MapQTL 6.0 software (Van Ooijen et al , 2000) as described previously (Koech et al 2018; Koech et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Maritim et al (2016) reported a significant upregulation of drought-related genes such as heat shock proteins (HSP70), superoxide dismutase (SOD), gene catalase (CAT), ascorbate peroxidase (APX), calmodulin-like protein (Cam7) and galactinol synthase (Gols4) in drought tolerant as compared to drought sensitive tea cultivars. Further, three major enzymes, namely transferases, hydrolases and oxidoreductases are involved in flavonoid biosynthesis, alkaloid biosynthesis, ATPase family proteins related to abiotic/biotic stress response have been identified (Koech et al, 2019). However, plants have evolved various antioxidative systems to keep the levels of ROS under control (Mittler, 2002).…”
Section: Genomic Responsesmentioning
confidence: 99%
“…Different marker systems such as randomly amplified polymorphic DNA (RAPD), restriction fragment length polymorphism (RFLP), amplified fragment length polymorphism (AFLP), sequence tagged sites (STS), single-strand conformation polymorphism (SSCP), inter simple sequence repeat (ISSR), simple sequence repeat (SSR) or microsatellite, Diversity Arrays Technology (DArT) microarray and chloroplast DNA (cpDNA) have been developed and applied in tea breeding (Wachira et al, 2001;Mondal et al, 2004;Chen et al, 2007;Sharma et al, 2009;Wambulwa et al, 2016aWambulwa et al, ,b, 2017Koech et al, 2018Koech et al, , 2019. These markers have been applied in genetic studies relating to assessment of genetic diversity and germplasm characterization, genotype identification and fingerprinting, estimation of genetic distances between populations, assessment of mating systems, detection of quantitative trait loci (QTLs), and marker-assisted selection (MAS) in tea (Wachira et al, 1995(Wachira et al, , 1997Paul et al, 1997;Hackett et al, 2000;Muoki et al, 2007;Kamunya et al, 2010;Koech et al, 2018Koech et al, , 2019. Most attributes of agricultural importance frequently manipulated by plant breeders (e.g., size, shape, yield, quality, tolerance to abiotic, and sometimes biotic stresses) display a quantitative mode of inheritance and normally exhibit continuous variation (Collard et al, 2005).…”
Section: From Conventional To Molecular Breedingmentioning
confidence: 99%
“…Then, a high-density SNP linkage map was constructed, and QTLs related to flavonoids that were dependent on the F1 population (LJ43 × BHZ) were identified in 2018 12 . Candidate QTLs and proteins were shown to be involved in flavonoid biosynthesis using DArTseq markers via two F1 populations (TRFK 303/577 × GW Ejulu and GW Ejulu × TRFK 303/577) in 2018 and 2019 33,34 . SNPs and InDels were identified based on whole genome sequences of 'Shuchazao' and 'Yunkang 10' in 2019.…”
Section: Discussionmentioning
confidence: 99%